Cell surface tension, the mobility of cell surface receptors and their location in specific regions - Mierke, Claudia (Physics of Cancer, Volume 1, 2018)
The shape fluctuations of the cell membrane that occur in all cells are continuously detected and hence are proposed to determine the function of the membrane. Although it has been shown how membrane fluctuations are affected by cellular activity in adherent cells, the spatial regulation of these fluctuations and the associated alterations in the mechanical properties of the membrane are still not clearly understood. The cell surface tension seems to play a crucial a role on the selection of an aggressive and invasive cancer cell subpopulation that is able to disseminate from the primary tumor in the microenvironment and propagate through all the steps of the metastatic cascade for the malignant tumor progression. Similar to cells rounding up during mitosis, cancer cells enhance their surface tension through an increase of the contractile actomyosin cortex based on elevated internal hydrostatic pressure. In the scenario of a liquid cellular interior, the surface tension is purely related to the local curvature and the hydrostatic pressure difference by Laplace's law. Moreover, the classical differential adhesion hypothesis fails in describing the experimental results and it is refined by including surface tension. The diffusion on the cell surface is not purely Brownian motion, as the mobility of cell surface receptors and their structural organization in special compartments (regions) within the cell surface membrane is constrained. These confinements restrict the lateral motility of cell surface receptors and are hence termed lipid rafts. The impact of these confinements alters the entire motility of cancer cells. Moreover, the location of cell surface receptors within the membrane and their anchoring to the cell's actomyosin cytoskeleton affects cellular mechanical properties such as membrane fluctuations. Although the actin polymerization or myosin II activity individually increases fluctuations, the cortex in unperturbed cells stretches out the cell membrane and thereby dampens membrane fluctuations. When these fluctuations are fitted with common models, the dampening of these fluctuations is provided by the spatial confinement of the cell's cortex. However, decreased fluctuations during mitosis or upon ATP-depletion/stabilization of actomyosin cortex are associated with elevated surface tension. Fluctuation maps of the cell membrane and also local temporal autocorrelation functions both reveal ATP-dependent transient short-range (less than 2 mu m) heterogeneities. However, it is still elusive what role these fluctuation heterogeneities play during the malignant progression of cancer.
CRIS-Team WoS Importer:2019-08-27